ETHNIC DIVERSITY OF BANTENESE SOCIETY - Humaeni, Ayatullah (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Ethnic Diversity of Bantenese Society